Religious Spiritual and Psycososial Coping Training (RS-PCT) Meningkatkan Penerimaan Diri dan Efikasi Diri pada Pasien Paska Stroke - Kelana Kusuma Dharma; Andi Parellangi; Halina Rahayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the effectiveness of Religious Spiritual and Psychosocial Coping Training (RS-PCT) interventions on self-acceptance and self-efficacy in post-stroke patients. The research method used in this study was an experimental design with a Randomized Control Trial (RCT) pre and post-test control groups. The results of this study showed that there were significant differences in self-acceptance (p = 0.046) and self-efficacy (p = 0.030) after treatment between the RS-PCT and control groups. The multi-analysis of covariance test showed only interventions (RS-PCT) that were significantly related to self-acceptance (p = 0.045) and post-stroke self-efficacy (p = 0.030) after being controlled by confounding variables (age, sex, type of stroke, aphasia, hemiparesis side). In conclusion, RS-PCT intervention is effective in increasing self-acceptance and self-efficacy in post-stroke patients who are recovering at home. Keywords: Self-Efficacy, Spiritual Religious Coping, Self-Acceptance, Psychosocial